The internationalization of the Renminbi and the rise of a multipolar currency system - Miriam Campanella (European Centre for International Political Economy (ECIPE), 2014)
The dollar's steady depreciation has had little impact on the official reserves of central banks. As scholars of the international monetary system debate whether the dollar can continue to play the dominant role in the international monetary system, actual developments in exchange relations already give reason to expect that the world's currency regime is changing. Recent measures taken by China to internationalize its renminbi, including several bilateral swap agreements signed with other central banks, have reinforced other eastward trends in the world economy. In this paper, China's acceleration of renminbi internationalization is examined. The growth of renminbi-based trade and settlements has made it Asia's new reference currency, surpassing the US dollar. These developments are mostly due to the effects of the financial crisis and have been supported by the region's economic and financial integration. As a reference currency of necessity or choice, the emergence of the renminbi in Asia is set to weaken the current global dominance of the US dollar. In conclusion, the paper makes the case that the growth of the renminbi as an international currency could generate a multipolar currency system that balances and distributes responsibilities in a better way than the current currency regime.
Keywords: F02; F33; 330; China; Renminbi; international monetary system; capital account liberalizisation; reserve currency; Renminbi; Internationales Währungssystem; Kapitalverkehrskontrolle; Reservewährung; China